Indentation Creep and Microstructure Properties of Sn-Ag Solder Alloys - Yassin, Amal Mohamed; Khalifa, B.A.; Ismail, R. Afify (JOURNAL OF ADVANCES IN PHYSICS, 2019)
The microstructure and micro-hardness of Sn-3.5wt.5%Ag, Sn-3.5wt.%Ag-0.27wt.%Ti and Sn-3.5wt.%Ag-0.27wt.%Cd treated at 75, 100, 125 and 150oC were studied. The microstructure characteristics of the tested alloys had been investigated using optical microscope (OM), scanning electron microscope (SEM) and x-ray diffraction (XRD). The impression creep had been carried out using Vickers micro-hardness indenter under different loads (10, 50 and 100gm). The stress exponent values were found to be varied from 3.2 to 8.4. The energy activating the creep processes support dislocation climb as the rate controlling mechanism. The dislocation mobility was restricted due to the agglomerations of the Ag3Sn eutectic phase in the above three solders. Whereas; the presence of the twinning of ?-Sn phase, and the dispersion of fine CdSn1.9 IMCs throughout Sn-3.5wt.%Ag-0.27wt.%Cd made strongly blockage of the dislocation motion.